Pengaruh Inventory Intensity, Kepemilikan Institusional dan Transfer Pricing terhadap Tax Avoidance - Rahmawati Rahmawati; Wiwit Irawati (Monex: Journal of Accounting Research, 2023)
This study aims to determine the effect of inventory intensity, institutional ownership and transfer pricing on tax avoidance simultaneously and partially. This research was conducted with a population of manufacturing companies in the consumer goods sector listed on the IDX for the period 2017-2021 totalling 104 companies. The sampling mechanism used a purposive sampling technique so that the sample obtained amounted to 85 samples. The research method used is an associative research method with a quantitative approach and uses secondary data. The results of this study found that inventory intensity, institutional ownership and transfer pricing simultaneously affect tax avoidance. Inventory Intensity affects tax avoidance partially, institutional ownership has no effect on tax avoidance partially and transfer pricing has no effect on tax avoidance partially.